Tobacco consumption influence on spending patterns within Costa Rican households - Sequeira Benavides, Erick Enrique (2024)
Tobacco consumption implies a dilemma in the allocation of the family budget. Hence, the objective of this study is to determine the effect of tobacco consumption on expenditure patterns within Costa Rican households. The 2018 National Household Income and Expenditure Survey is used to estimate Engel curves through a Quadratic Almost Ideal Demand System, using the Seemingly Unrelated Regression model for a set of 11 expenditure categories. Due to heteroskedasticity and endogeneity, the Generalized Method of Moment Three-Stage-Least-Squares (GMM-3SLS) is used since it provides more efficient parameter estimates. Results show that tobacco consumption is associated with a crowding-out effect on health expenditure and with a crowding-in effect on restaurant and hotel expenditures. Furthermore, tobacco consumption shows a crowding-in effect on alcoholic beverages for every income quintile. This suggests that tobacco consumption could harm the country´s standard of living and not only the realm of health.